Follow the red road of triheme cytochromes in Geobacter sulfurreducens - Dantas, Joana Margarida Franco (2012)
The bacterium Geobacter sulfurreducens (Gs) is capable of oxidizing a large variety of compounds relaying electrons out of the cytoplasm and across the membrane in a process designated as extracellular electron transfer. The Gs genome was fully sequenced and a family composed by five periplasmic triheme cytochromes c7 (designated PpcA-E) was identified. These cytochromes play an important role in the reduction of extracellular acceptors. They contain approximately 70 amino acids, three heme groups with bis-histidinyl axial coordination, and share between 57 and 77% sequence identity. The triheme cytochrome PpcA is highly abundant in Gs and is most likely the reservoir of electrons destined for outer surface. In addition to its role in electron transfer pathways this protein can perform e-/H+ energy transduction, a process that is disrupted when the strictly conserved aromatic residue phenylalanine 15 is replaced by a leucine (PpcAF15L). This Thesis focuses on the expression, purification and characterization of these proteins using Nuclear Magnetic Resonance and ultraviolet-visible spectroscopy. The orientations of the heme axial histidine ring planes and the orientation of the heme magnetic axis were determined for each Gs triheme cytochrome. The comparison of the orientations obtained in solution with the crystal structures available showed significant differences. The results obtained provide the paramagnetic constraints to include in the future refinement of the solution structure in the oxidized state. In this work was also determined the solution structure and the pH-dependent conformational changes of the PpcAF15L allowing infer the structural origin for e-/H+ energy transduction mechanism as shown by PpcA. Finally, the backbone and side chain NH signals of PpcA were used to map interactions between this protein and the putative redox partner 9,10-anthraquinone-2,6-disulfonate (AQDS). In this work a molecular interaction was identified for the first time between PpcA and AQDS, constituting the first step toward the rationalization of the Gs respiratory chain.